A Bayesian framework perspective for model of paired comparison in cricket teams ranking - Alkhezi, Hajar M.; Shafee, Ahmad; Alkhezi, Yousuf (Frontiers in Applied Mathematics and Statistics, 2025)
Ranking cricket teams are crucial in determining their standing and precedence in international cricket. In this study, we propose a novel approach to assess cricket team rankings using the Bayesian paired comparison method. The Bayesian paired comparison method is a statistical technique that leverages subjective assessments from a group of teams to evaluate their relative performance. The proposed approach is compared with the official rankings provided by the International Cricket Council (ICC), and it is found that the results obtained from the Bayesian method closely align with the ICC rankings. By incorporating subjective assessments and leveraging Bayesian inference, the method proves to be a reliable and accurate tool for evaluating team performance. The study highlights the advantages of the Bayesian paired comparison approach over traditional statistical techniques and provides valuable insights for cricket administrators, coaches, and enthusiasts in assessing and comparing the performance of cricket teams.